An analysis of orbital fracture in open-clinic practice of Department of Ophthalmology Medical University of Gdansk 1990-1991 and 2000-2001 years - Homziuk, Magdalena (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Orbital fractures are common in midface trauma. The aim of our study was the retrospective analysis of patients with eye injuries. According to a prospective protocol we studied 82% adults and 18% children with orbital fractures. Men compared 72% of the patients. Men aged 21-35 years the most affected (mean age 29 years). These patients were divided into two groups: these who was treated in Emergency Department of our Clinic in 1990-1991 years (group I) and these who was treated in 2000-2001 (group II). Patients were analysed for age, sex, cause of injury and types of orbital fracture. In a patient with orbital trauma and orbital fractures visual acuity and ocular muscle motility are two most important ophthalmologic functions to be evaluated emeregently. Inclusion criteria were clinically suspected orbital injuries defined by reduced bulbus motility or diplopia We determined visual function: visual acuity, intraocular pressure, biomicroscopy and ophthalmoscopy, X- ray and CT examination. X- ray and CT has come to play a major role in the orbital examination of trauma patients with orbital fractures. Our cases of the orbital margin fractures classified into: blow-out (orbital floor fracture), Le Fort III (orbital- zygomatic fractuer), roof fracture (racture of the inferior orbital rim) and complex orbital fracture. The blow-out orbital fracture was the most common fracture type and orbital roof was the least common site of fracture of the orbital bony covering of the eye. In whole orbital fractures there were single wall fracture in 43% of cases in group I and 41% of cases in group II., two-wall fracture in 31% of cases in group I and 30% of cases in group II, Three wall-fracture in 15% of cases in group I and 17% of cases in group II. and four wall-fracture in 11% of cases in group I and 12% of cases in group II. Of whole orbital fractures had an associated eye injury. Common mechanisms included assaults (37% of cases in group I and 46% of cases in group II) and car or motor vehicle accidents (43% of cases in group I and 44% of cases in group II). We believe that further studies on this subject are necessary because the mechanism which produces the orbital fractures is subject to debat, they are acknowledged to be difficult to diagnose solely through clinical means.